Did Trust in Government Induce the Impact of Loneliness and Self-Control on Student’s Compliance during Social Restriction Implementation? A moderator analysis - Rahmadianty Gazadinda; Mia Fattah Rizki; Rayi Hamam Azka; Erin Andriani Putri; Margareta Damayanti; Fajar Wahyu Utomo (Universitas Ahmad Dahlan, 2024)
The mitigation strategy employed in addressing the prolonged pandemic situation in Indonesia yielded a discernment: collaborative efforts between individuals and the government were imperative to achieve the desired objectives. Despite the emergence of numerous psychological challenges among individuals during the pandemic, the pivotal role of public compliance became particularly evident during the implementation of social restrictions. Government initiatives to mitigate risks would not attain optimal effectiveness without substantial support from the public, either through trusting the government or adhering to regulatory measures. This study seeks to elucidate the moderating role of government trust in the impact of loneliness and self-control on students' compliance with social restriction policies during the Covid-19 pandemic. Conducted in early 2022 using a cross-sectional design, the study encompassed 401 undergraduate students from various regions in Indonesia. Employing Moderated Regression Analysis (MRA), the results demonstrated that trust in the government significantly moderated the effects of loneliness and self-control on student compliance (F(6, 403) = 101.017, p<0.001). The findings revealed that students were more inclined to comply with social restriction policies, even when experiencing loneliness, if they maintained trust in the government. This study underscores the significant role of government trust, particularly in situations necessitating cooperative behavior from the public in adhering to policies.